RIGHT TO REPAIR SEBAGAI PERLINDUNGAN KONSUMEN ELEKTRONIK DALAM PERWUJUDAN EKONOMI SIRKULAR - Muhammad Raidendy Prihasto (2022)
Limitations of consumers in repairing their electronic goods with respect to access to information and original spare parts components caused by electronic manufacturing controls, in the presence of indications of market domination efforts. From restrictions on sales of Original Equipment Manufacturer (OEM) spare parts, restrictions on repairs from third-party independent repair shops and closed access to information in repairing electronic components and the creation of electronic goods with predatory designs that can be damaged easily. Placing consumers on the powerlessness of business actors. Whereas Article 7 letter b of Law Number 8 of 1999 concerning Consumer Protection (Consumer Protection Law) states that business actors are required to provide instructions for use, repair and maintenance, and Article 25 states that business actors are required to provide spare parts. However, the actualization of the article has not been optimized properly and there is not enough supervision on the spare parts market and repair services. So this paper will discuss the problems of electronic producer schemes in reducing consumer rights and solutions that can be done regarding these problems in order to realize a circular economy. The research method uses a normative juridical approach and a comparative study using qualitative research with secondary data. As for the solution that can be done is through the government to enforce the law on the Consumer Protection Act; amendments to Permendag 26 of 2021 regarding the increase in the after-sales obligation period for spare parts and the obligation to provide maintenance and repair guidelines; reformulation of Article 44 of the Copyright Law regarding reasonable interests; implementation of the Repair and Durability Rating system regarding the detail level of repair on electronic products; implementation of obligations to producers in order to be able to sell spare parts to consumers and MSMEs